Application of a stream-aquifer water quality interaction model to a site in the Thames Basin - 347705 Norhan Abd. Rahman; University of Newcastle Upon Tyne (Newcastle upon Tyne : University of Newcastle upon Tyne, 1991)
Mathematical models for the study of groundwater quality changes are based on the equations of flow and mass transport. Such models can describe how the groundwater responds to, or is affected by waste contaminants through hydraulic interaction with polluted surface waters or directly through injection wells and spreading basins or seepage form waste disposal sites. This study describes the application of model of flow and solute transport to the Gatehampton site (a public water supply wellfield) that extracts water form the Chalk aquifer adjacent to the Thames river. The model used is a computer based numerical model (UNCLESAM) developed by Dr. P.L Younger(1990). The Thames river is found to provide induced recharge to the aquifer during pumping of the wellfield. The aim of the modelling was to examine the likehood a pollution by contaminated river water and to further explore the sensitivity of the results to various hydraulic parameters of the streambed and aquifer. However, difficulties in getting the software operational and the time taken to review of the conceptual mdoel underpinning the development of UNCLESAM has meant that the study has only been able to address the flow characteristic of the site.